Osteoporosis: how long to treat? - Adler, Robert A. (Henry Stewart Talks, 2015)
The commonness of fractures due to osteoporosis, Positive and negative effects of treatment (bisphosphonates & others), Review of long term studies, Individualizing treatment
Archived at 2024/06/30